Density Functional Based Tight Binding Study on Wurzite Core-Shell Nanowires Heterostructures Zno/Zns - Thuong, Nguyen Thi; Minh, Nguyen Viet; Tuan, Nguyen Ngoc; Tuoc, Vu Ngoc (Communications in Physics, 2011)
We present a Density Functional Based Tight Binding study on the crystallography and electronic structures of various II-VI wurtzite core-shell, core-multi-shell ZnO/ZnS unsaturated nanowires (NW) of circular and hexagonal cross sections and examine the dependence of interface stress and formation energy on nanowire lateral size with diameter range from 20$\mathring{A}$ upto 40$\mathring{A}$. Young's modulus of the wires along the axial growth direction have been estimated. Also the tensile tests have been applied for various wires to show the diameter dependences of their mechanical properties. The electronic properties of these heterostructure nanowires (e.g., Projected Band Structure, Density of State, charge transfer via Mulliken population analysis) also exhibit diameter-dependent behavior.